The Strategy to Increase Consumer Protection in the Fintech Industry through Progressive Regulation and Digital Financial Education - Yuwono, M. Sunandar; Sara, Rineke (Ridwan Institute, 2025)
The development of financial technology (fintech) in the digital era has brought significant changes in financial services, providing easy access and efficiency for consumers. However, behind the benefits offered, there are various legal challenges related to consumer protection, including the risk of misuse of personal data, online fraud, and unclear dispute resolution mechanisms. Regulations governing the fintech sector are still evolving to adapt to the dynamics of rapidly changing technology. Therefore, it is vital to analyze how legal protection for consumers in the fintech sector in Indonesia is implemented and how existing regulations can provide legal certainty for the community. This research employs a normative juridical methodology that combines a conceptual and statutory approach. The Electronic Information and Transactions Law (ITE), Law Number 8 of 1999 concerning Consumer Protection, and other regulations of the Financial Services Authority (OJK) and Bank Indonesia pertaining to the fintech ecosystem in Indonesia were among the pertinent regulations that were analyzed. This study also looks at regulatory developments in the digital age and legal theories pertaining to consumer protection in electronic transactions. This study uses a normative legal approach to better understand the legal protections for consumers in fintech transactions and to pinpoint implementation issues. It is anticipated that the study would help create policies that are more adaptive to technological developments and provide recommendations for more effective legal policies in protecting consumers in the fintech era.